Mixed-metal organic framework-coated ZnO nanowires array for efficient photoelectrochemical water oxidation. (28th January 2019) - Peng, Zhen; Abbas, Syed Comail; Lv, Jiangquan; Yang, Rui; Wu, Maoxiang; Wang, Yaobing
Abstract: Designing of high-performance photoanodes is essential for efficient solar energy conversion in photoelectrochemical (PEC) water splitting. Herein, we report an effective approach to synthesize three dimensional (3D) mixed-metal organic framework-coated ZnO nanowires array (ZnNi MOF@ZnO) for the effective PEC performance. The ZnO nanowires act as photon absorber as well as rapid charge transporter; whilst the ZnNi MOF provides the active sites for PEC process by lowering the energy barrier of water oxidation and suppressing electron-hole recombination. The 3D nanostructure of ZnNi MOF@ZnO nanowires array provides intimate interfacial contact through covalent interactions between the ZnNi MOF and ZnO nanowires which facilitates the rapid charge transfer during photocatalytic oxygen evolution reactions. As a result, the ZnNi MOF@ZnO nanowires array exhibited excellent photoelectrochemical water oxidation with very low onset potential (0.31 V vs. RHE) and high photocurrent density (1.40 mA/cm 2 ) as compared to the Zn MOF @ZnO and ZnO nanowires array. This facile strategy provides a promising direction towards high performance photoanode design for adequate solar energy conversion. Graphical abstract: Highlights: ZnNi MOF@ZnO is an efficient anode for photoelectrochemical OER. ZnNi MOF@ZnO is synthesized via a facile two-steps hydrothermal method. OER on ZnNi MOF@ZnO shows 0.31 V onset potential and 1.4 mA/cm 2 photocurrent density. Thin layer ZnNi MOF facilitates charge separation and transfer efficiency during OER.